Strategi Pemberdayaan Masyarakat dengan Metode Sustainable Livelihood Approach (Studi Kasus Kampung Waramui Distrik Sidey Kabupaten Manokwari - Dedi Riantoro; Maria M. Semet (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2018)
Rural areas are places where communities are very close to natural resources and the environment because the villagers suspends their lives by relying on natural and environmental assets such as land, forests, springs and other products. The aim of this research is to identify the existing assets in Waramui village, access, vulnerability, and to analyze the empowerment strategy of Waramui villagers by using SLA (Sustainable Livelihood Approach) approach in Waramui Village, Sidey District, Manokwari. The research method used is descriptive qualitative method that is xplorative. Data collection methods used are primary data and secondary data then the data is analyzed using simple frequency tabulation. In the research results can be known assets, social relations, vulnerability, and institutions in Waramui village showed almost 72.09% of people depend on nature. The SLA Strategy (Sustainable Liveliihood approach) that can be done in Waramui village is by utilizing the natural products by converting the raw product into a value-added product and the cooperation between the community, the chief of the tribe and the head of village to utilize the assets, social relations, institution in Waramui village.